ANALISIS KETERKAITAN KESIAPAN BELAJAR MATEMATIKA SISWA TERHADAP KEMAMPUAN KOMUNIKASI MATEMATIKA SISWA SELAMA MASA PANDEMI COVID -19 - Jelita Elperika Sihombing; Roslian Lubis; Sinar Depi Harahap (Program Studi Pendidikan Matematika Institut Pendidikan Tapanuli Selatan, 2022)
This study aimed to analyze the linkages between students ' mathematics learning readiness and students' mathematics communication ability during the Covid -19 pandemic at SMP Negeri 1 Sosorgadong. The approach of the research applied qualitative descriptive. Questionnaire, test, and interview were used in collecting the data. The technique of data analysis used triangulation. The source of the data is 10 students and 3 students is the subject of the research. The result of the research shows the students' physical condition is good in teaching learning, the average of students’ learning readiness is 69.2 (enough category), and the average of students' mathematics communication ability is 66.33 ( enough category). The linkages between students ' mathematics learning readiness and students' mathematics communication ability during the Covid -19 pandemic at SMP Negeri 1 Sosorgadong includes students who has high mathematics learning readiness has high mathematics communication skills, students who has enough mathematics learning readiness has medium mathematics communication skills, and students who has low mathematics learning readiness has low mathematics communication skills.